Application and limitations of batteries and hydrogen in heavy haul rail using Australian case studies. (1st December 2022) - Knibbe, Ruth; Harding, Damien; Cooper, Emily; Burton, Jonathan; Liu, Sheng; Amirzadeh, Zhila; Buckley, Roger; Meehan, Paul A.
Abstract: Decarbonisation of heavy haul rail is an essential contributor to a zero-emissions future. However, the transition from diesel to battery locomotives is not always practical, given the unique characteristics of each haul. This paper demonstrates the limitations of state-of-the-art batteries using real-world data from multiple locomotives operating in Australian rail freight. An energy model was developed to assess each route's required energy and potential regenerated energy. The tractive and regenerative battery energy, mass, and cost were determined using data from the energy model coupled with battery specifications. The feasibility of implementing lithium iron phosphate (LFP), nickel manganese cobalt (NMC) and lithium titanium oxide (LTO) chemistries was explored based on cost, energy density, cycle lifespan and locomotive data. LFP was identified as the most suitable current battery solution based on current chemistries. Further examination of the energy demands, and associated mass/volume constraints concluded that three platforms are required for heavy haul rail decarbonisation i) a battery electric locomotive for low-energy demands, which can be coupled with either ii) a battery electric tender for medium energy demands or iii) a hydrogen fuel cell electric tender for higher energy demands. A future-looking techno-economic assessment of battery and hydrogen fuel cell platforms concludes that the lowest cost solution for low-energy hauls is a battery-only system, and for high-energy hauls, a battery-hydrogen system. Highlights: A large dataset is used to assess the energy requirement for 12 different heavy haul rail routes. The regenerative braking potential in heavy haul rail is significant from 21% – 55% of the total route energy. Due to cost, energy density and durability, LFP is considered the most suitable battery chemistry for heavy haul rail. On-board cooling reduces battery degradation and accounts for an additional ca. 4% of the total energy required. For high energy routes, a hydrogen electric tender is assessed to be more feasible rather than a battery electric tender.